Developing Feasible and Effective School-Based Interventions for Children With ASD: A Case Study of the Iterative Development Process. (March 2015) - Dykstra Steinbrenner, Jessica R.; Watson, Linda R.; Boyd, Brian A.; Wilson, Kaitlyn P.; Crais, Elizabeth R.; Baranek, Grace T.; Flippin, Michelle; Flagler, Sally
Despite an emphasis on identifying evidence-based practices among researchers and using evidence-based practices among professionals in the field of education, there are still problems with uptake and implementation in real-world settings. This lack of diffusion of practices is evident in educational programming for children with autism spectrum disorder (ASD). One solution is to use an iterative process to develop interventions in which researchers work in collaboration with the end users to test and refine interventions. However, there are very few guidelines for developing feasible and effective interventions through these iterative processes. This article provides a description of the iterative process used to develop the Advancing Social-Communication and Play (ASAP) intervention, a supplemental program designed for public preschool classrooms serving students with ASD, and examples of how data from the sequence of iterative design studies shaped the intervention development. The research team offers guidelines for other researchers looking to engage in intervention development using an iterative process in the context of partnerships with end users, including suggestions for planning and executing an intervention development grant.